Combined Association of Tumoral PD-L1 Expression and Pretreatment Presence of Epstein-Barr Virus DNA With Risk Stratification and Prognosis of Patients With Nasopharyngeal Carcinoma - Li, Xiaoyu; Peng, Xingchen; Zhao, Sha; Zhang, Hong; Jiang, Yong; Liu, Fei; Ai, Ping (Frontiers in Oncology, 2022)
Background: Little is known about whether the combination of tumor programmed death-ligand 1 (PD-L1) expression and pretreatment EBV DNA status can help stratify nasopharyngeal carcinoma (NPC) patients by risk of metastasis or predict prognosis. Methods: PD-L1 expression was assessed using immunohistochemical staining of 78 non-keratinizing NPC patients with clinical data. Survival outcomes and independent prognostic factors were identified. Results: Seventy-eight patients were included, high PD-L1 expression was observed in 25 of 43 patients (58%) with metastasis, while it was observed only in 7 of 35 patients (20%) without metastasis. Multivariate analyses showed that progression-free survival (PFS) was independently predicted by tumoral PD-L1 expression and pretreatment EBV DNA status. When combining, 93.75% patients with high PD-L1 and EBV infection developed distant metastasis, and those patients were associated with worse PFS. Conclusions: Both PD-L1 expression and pretreatment EBV DNA are closely related to metastasis and prognosis of NPC patients. Their combination can facilitate risk stratification and prognosis prediction, which may improve disease treatment and management.